Drawing in-situ: Matters of care and representation in daily life with dementia. (June 2023) - Cleeve, Helena; Borell, Lena; Rosenberg, Lena
This article brings methodological insight into in-situ drawings as representations of daily life with dementia. As part of ethnographic fieldwork in dementia care units in a nursing home, drawings were made on site by a researcher. We suggest that the ambiguity of in-situ drawings, and the ensuing possibilities to disambiguate them, is valuable. Inspired byAsdal and Moser's (2012) concept of "contexting, " we experimented with arranging the drawings with fieldnotes, discussing them with staff members, as well as with configuring multiple drawings and fieldnotes in sequences. This led to reflexive engagements with the drawings, creating space for discussing concerns in research practices and care practices. Switching between different forms of contexting produced tensions, revealing that what was cared for through the practices of researchers, staff members, and residents, diverged. In this way, we argue that contexting in-situ drawings may intervene in ways of knowing, caring for, and living with dementia.